The experiential value of gambling in f2p gamespaces - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2025)
This article explores the experiential value of gambling within free-to-play (f2p) gamespaces. In doing so, it offers a more balanced understanding of the gambling/gaming interplay. Whilst existing understandings tend to focus on the assumedly predatory monetisation techniques that players are subjected to by game developers, I instead argue that a logic of gambling is integral to the f2p experience economy of Asian players. Drawing on an analysis of in-depth interviews with Singapore-based game players/developers, I show how the virtual items and worlds that players engage with through f2p gamespaces are imbued with experiential value, whilst developers leverage the volumes of data generated by players to maximise this value in ways that might eventually lead to their monetisation. Embracing these complementary facets of f2p gamespaces can help expand normative understandings of gambling in/and gaming.